2014
DOI: 10.1097/scs.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

Caries Management By Risk Assessment in a Cleft and Craniofacial Center

Abstract: Patients with craniofacial anomalies have an increased incidence of dental caries. The prevention program "Caries Management By Risk Assessment" (CAMBRA) has been previously validated but has not yet been introduced at a widespread level in a medical setting, particularly for this high-risk population.In this cross-sectional study, we aimed to evaluate the feasibility of implementing CAMBRA during the medical visit at an institutional tertiary care center, which treats children with craniofacial anomalies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Fourteen studies, including an epidemiological survey, and cross-sectional, case-control, prospective and observational studies, showed the same pattern compared to those that analysed these parameters separately. 16,35 The use of fluoride products was reported in a variety of studies, [4][5][6]8,12,16,21,29,34 and some of them showed that this was higher in CLP patients than in controls. 6,12,23,35,38 This was observed in patients in different phases of oral development, and it was similar in the primary, mixed and permanent dentitions, suggesting that the increased risk of oral problems persists.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen studies, including an epidemiological survey, and cross-sectional, case-control, prospective and observational studies, showed the same pattern compared to those that analysed these parameters separately. 16,35 The use of fluoride products was reported in a variety of studies, [4][5][6]8,12,16,21,29,34 and some of them showed that this was higher in CLP patients than in controls. 6,12,23,35,38 This was observed in patients in different phases of oral development, and it was similar in the primary, mixed and permanent dentitions, suggesting that the increased risk of oral problems persists.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, the selected articles included information on the bacterial plaque indexes, 3,10,17-20 the prevalence of dental caries 1,5,9,14,16,21,22,24,[29][30][31][32] and on both plaque indexes and dental caries. In this review, the selected articles included information on the bacterial plaque indexes, 3,10,17-20 the prevalence of dental caries 1,5,9,14,16,21,22,24,[29][30][31][32] and on both plaque indexes and dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations